Utilisation of ultra-low grade waste heat from vc (vapour compression) cycle for LDAC application - Muhammad Fazil Kamis (2014)
The report describes the comparison of the conventional air conditioning system against that of liquid desiccant air conditioning (LDAC) system. For the past recent years, LDAC has been the main focus of most research efforts due to its advantages in utilising low grade waste heat as its main driving energy. A comparison between the various types and forms of liquid desiccants was mode to determine the most suitable and efficient desiccant for the dehumidification process.